Empirical Study on the Influencing Factors of Liquidity Risk in International Money Market Funds - Yu, Xue; Chen, Shunshun (International Journal of Global Economics and Management, 2024)
In the past two years, new funds issuance has been extremely hot, and the total scale of public offering funds has also increased significantly. Behind the extremely hot issuance of new funds, it also gave birth to a number of “hotstyle” funds. But at the same time, a number of “hotstyle” funds have also encountered a large number of redemption phenomenon, making a large number of young investors get the title of “leek zero”. This paper returns the quarterly data of 28 money market funds, analyzes the factors affecting money market fund liquidity risk, and obtains the relationship between each influencing factor and the liquidity risk of money market fund. Then it put forward the establishment of a liquidity monitoring an dearly warning mechanism for money market funds, strengthen the risk tips for investors and improve the subscription and redemption fees.